Politics and Persuasion in Plato: Some Preliminary Considerations - Mauricio Garcia Dotto, Pedro (Revista Archai, 2024)
In this paper, I focus on the problem of persuasion in Plato’s work and expound on its philosophical, political, and educational implications. I begin by tracing an overview of persuasion in Ancient Greece, both the persuasive activity and the mythical figure of the goddess Persuasion. Then, I dwell on some emblematic cases of the failure of Socratic persuasion. Next, I aim to reconstruct some causes that emerge in the Platonic dialogues to explain the failure of Socratic persuasion. Finally, I consider the vindication of rhetoric for philosophy, defended and developed in the Phaedrus, as a response to the impasse that truth is not self-evident and, therefore, cannot be transmitted immediately and mechanically from one soul to another.